Analysis of the Influence of Work Motivation and Work Environment on Employee Performance: Case Study at PT. Panja Multi Mineralindo - Prastyo Wibowo, Nugroho; Amal, M Khairul; Abdul Aziz, Muh (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to analyze the influence of work motivation and work environment on employee performance at PT. Panja Multi Mineralindo, a company engaged in mining and natural stone crushing. This study uses a quantitative approach with a census method or saturated sample, involving the entire population of 77 employees. Data were analyzed using multiple linear regression with the help of SPSS software version 25. The results of the study indicate that there is a positive and significant influence between work motivation and employee performance, as well as a positive and significant influence between work environment and employee performance. In addition, work motivation and work environment simultaneously affect employee performance. The Adjusted R² value of 0.431 indicates that 43.1% of employee performance variation can be explained by work motivation and work environment, while the rest is influenced by other variables not studied. This study provides important implications for company management to increase motivation and create a conducive work environment in order to improve employee performance.